Mindfulness Therapy Affects Anxiety Levels in Pre-Cardiac Catheterization Patients - Handayani, Prita Adisty; Sutanti, Yuni; Palupi, Pipin; Susilowati, Widhi; Setiawati , Devinta Dwi; Anjili, Rialista (Poltekkes Kemenkes Aceh, 2025)
Background: Cardiac catheterization is an invasive procedure that can cause various emotional reactions in patients, one of which is anxiety. This anxiety can arise due to pain and fear of the catheterization procedure involving a vital organ of the body, namely the heart. High levels of anxiety can have an impact on increasing blood pressure to decreasing oxygen saturation, so that it can affect the smoothness of the cardiac catheterization process itself. To overcome this, one of the non-pharmacological interventions that can be applied is relaxation therapy through mindfulness meditation. Purpose: To find out the effect of mindfulness on the anxiety level of pre-cardiac catheterization patients. Methods: Quantitative research type with quasi-experimental design with one group pretest-posttest design. The sampling technique used was accidental sampling. The sample in this study was 34 respondents with inclusion criteria, namely pre-cardiac catheterization patients with full consciousness and cooperation. The study was conducted from March to May 2024 by measuring anxiety levels using the Visual Analog Scale (VAS-A). Researchers measured the anxiety of pre-catheterization patients and provided mindfulness therapy intervention for 1 hour before cardiac catheterization, and took post measurements afterwards. Results: Based on the results of the Wilcoxon test, a p-value of 0.000 (<0.05) was obtained, which means that there is an influence of mindfulness therapy on the level of anxiety of pre-cardiac catheterization patients. Conclusion: After the intervention, there were 25 respondents who experienced a decrease in anxiety levels, 1 respondent experienced an increase, and 8 respondents with the same level of anxiety. The majority of anxiety levels after the intervention were at a moderate level.